2020
DOI: 10.1002/jnr.24744
|View full text |Cite
|
Sign up to set email alerts
|

Divergent membrane properties of mouse cochlear glial cells around hearing onset

Abstract: Spiral ganglion neurons (SGNs) are the primary afferent neurons of the auditory system, and together with their attendant glia, form the auditory nerve. Within the cochlea, satellite glial cells (SGCs) encapsulate the cell body of SGNs, whereas Schwann cells (SCs) wrap their peripherally-and centrally-directed neurites. Despite their likely importance in auditory nerve function and homeostasis, the physiological properties of auditory glial cells have evaded description. Here, we characterized the voltage-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 97 publications
1
2
0
Order By: Relevance
“…These ranged from extended spindles with small cell bodies, to more complex triangular or multipolar morphologies. Consistent with data from cultured mouse cochlear glia (Smith et al, 2020), the cells identified by S100 immunofluorescence were also labeled by an antibody targeting the transcription factor Sox10 (Fig. 1G).…”
Section: Sgns and Glial Cells Display Distinct Protein Expression Profiles And Morphologiessupporting
confidence: 85%
“…These ranged from extended spindles with small cell bodies, to more complex triangular or multipolar morphologies. Consistent with data from cultured mouse cochlear glia (Smith et al, 2020), the cells identified by S100 immunofluorescence were also labeled by an antibody targeting the transcription factor Sox10 (Fig. 1G).…”
Section: Sgns and Glial Cells Display Distinct Protein Expression Profiles And Morphologiessupporting
confidence: 85%
“… 22 ) in mid-modiolar vibratome sections prepared from cochleae of WT and Ndp- KO. At 1 month, using a Tubb3 antibody to label SGNs and a Kir4.1 antibody to label SGCs ( 23 ), there was no difference between the 2 genotypes in the density (number/area) and size of SGNs in basal, middle, or apical cochlear regions ( Figure 3, A–C ). As anti-Tubb3 showed increased background staining of cochlear connective tissue in Ndp -KO mice at 11–12 months (due to immunoreactivity with the secondary antibody targeting mouse IgG; data not shown), we used immunostaining for the neuronal intermediate filament Nf200 ( 24 ) and myelin basic protein (Mbp) to quantify the density and size of SGN cell bodies at this stage ( Figure 3, D–F ).…”
Section: Resultsmentioning
confidence: 99%
“…We also detected the glial cells, which comprise the satellite glial cells, glial precursor cells, and Schwann cells. The satellite glial cells, that express unique markers different from those expressed in the dorsal root ganglia ( 45 ), encapsulate the soma of spiral ganglion neurons and most likely maintain their excitability ( 46 ). They express genes encoding proteins involved in myelination, such as the myelin oligodendrocyte glycoprotein ( Mog ), myelin-associated glycoprotein ( Mag ), and myelin-associated oligodendrocyte basic protein ( Mobp ).…”
Section: Resultsmentioning
confidence: 99%